Prices Never Lie: Political Parties Contribution to High Cost of Election in Indonesia - Prianto, Andi Luhur; Inrinofita, Sari; Rosmita, Rosmita; Cortez, Estefanie R. (Politicon : Jurnal Ilmu Politik, 2025)
Indonesia has been transformed in developing more inclusive and participatory electoral mechanisms. However, the high cost of organizing elections has been a necessity. This article aims to explain the increase in electoral costs in periodic elections. The discussion focuses on the influence of political parties in increasing the political costs of elections, given that parties require costs for planning, campaigning and internal operations. This research uses a qualitative-explanatory approach, through data collection of official documents and media reports. The data that has been coded is then analyzed interactively, with the Nvivo 12 application. The results show that there is an increasing trend in the election budget, from the 2004 election to the last election in 2024. The increased costs follow the design of organizing elections and the response of political parties to the increase in campaign operational costs. The increase in electoral political costs is not followed by the structuring of the political financing system, proper supervision of party revenue sources, and rigorous transparency and accountability mechanisms. This article contributes to explaining the complexities and dynamics of electoral financing, focusing on the contribution of political parties in institutionalizing high-cost elections in Indonesia